Hypothalamus-Olfactory System Crosstalk: Orexin A Immunostaining in Mice - Gascuel, Jean; Lemoine, Aleth; Rigault, Caroline; Datiche, Frédérique; Benani, Alexandre; Pénicaud, Luc; López-Mascaraque, Laura (Frontiers in Neuroanatomy, 2012)
It is well known that olfaction influences food intake, and almost vice versa, the nutritional status of individuals modulates olfactory sensitivity. However, the neuronal correlate of this relationship and the connections between the olfactory bulb and the hypothalamus is still poorly understood. The goal of this report is to analyze the type of connections between the olfactory bulb and hypothalamus focusing on the expression pattern of orexin A, a hypothalamic neuropeptide that is thought to play a role in sleep/wakefulness states. Interestingly, orexin A has also been described as a stimulator of food intake. Such an effect may be due in part to the stimulation of the olfactory bulbar pathway. In rats, orexin positive cells are strictly concentrated in the lateral hypothalamus while their projections invade nearly the entire brain including the olfactory system. Therefore, orexin appears to be a good candidate to play a pivotal role in connecting olfactory and hypothalamic pathways. So far, orexin expression has been described in rats but there is still a lack of information concerning its expression in the adult and developing mouse brain. In this context we revisited the orexin A expression pattern in adult and developing mice using immunohistological methods and confocal microscopy. Besides minor differences, we found that the expression pattern of orexin A in mice shares many features with that in rats. In the olfactory bulb, even though there are few orexin projections, they reach all the different layers of the olfactory bulb. In contrast with the presence of orexin projections in the Main Olfactory Bulb almost none have been found in the Accessory Olfactory Bulb. The developmental expression of orexin A supports the hypothesis that orexin expression only appears post-natally.